ORAL LEUKOPLAKIA, THE FIRST CLINICAL FINDING OF ORAL SQUAMOUS CELL CARCINOMA (OSCC): A CASE REPORT - Embun Manja Sari; Fika Faradilla Drakel; Riani Setiadhi (FKG Unlam, 2022)
Background: Oral squamous cell carcinoma (OSCC) is preceded by oral potentially malignant disorders (OPMD). Oral leukoplakia (OL) is a non-scrapable white plaque lesion on oral mucosa and one of OPMD. Lack of knowledge about signs and symptoms of OPMD and health care providers are responsible for delays in establishing the diagnosis. Objectives: to improve health care provider’s knowledge and the importance of detecting leukoplakia as an early sign of malignancy. Case: A 30-year-old woman came to the oral disease clinic at Hasan Sadikin Hospital complaining of canker sores and a lump on right tongue that had not been healed since 3 months ago. She had history of chronic irritation on tongue which was bitten by linguoversion tooth 46. Intraorally there was a solid mass, irregular edge in lateral right tongueat region tooth 46, 1.5 x 0.5 cm in size and a white plaque at region 46-48, 11 x 10 mm in size, could not be scrapped, unpainful on touched but felt sore when eating and drinking. Based on anamnesis, extraoral and intraoral examination, the working diagnosis was suspected fibroma region 46 and OL region 46-48. Case management: Pharmacological manage,ment was povidone-iodine mouthwash and referred to Oral Surgery Department. Well-differentiated OSCC was made as definitive diagnosis, based on histopathological examination and CT-Scan which showed bilateral lymph nodes enlargement. The patient was referred to Haemato-oncology Department for chemotherapy. Conclusion: it is important to do histopathological examination and CT-Scan as an effort for establishing OL as the early sign of malignancy. Keywords : Oral cancer, Oral leukoplakia, Oral potentially malignant disorders